The Relationship between Health Behavior and General Health Status: Based on 2011 Korea National Health and Nutrition Examination Survey - Cheon, Chunhoo (2014)
OBJECTIVES: The aim of the present study is to investigate the relationship between health behavior and general health status. METHODS: We used data from the 2011 Korea National Health and Nutrition Examination Survey. Mental health was measured by stress recognition and depression. Dietary habit was measured by mixed grain diet. Life pattern was measured by sleeping time and working pattern. Physical activity was measured by walking and exercise. We defined general health status as Euro Quality of Life-5 Dimension (EQ-5D(index)), Euro Quality of Life Visual Analogue Scale (EQ-5D(vas)), number of people experienced lying in a sickbed for the last one month, number of days lying in a sickbed for the last one month, and activity limitations. RESULTS: Mental health, dietary habit, life pattern, and physical activity have seven factors. Most of the factors have a significant correlation with EQ-5D(index), EQ-5D(vas), number of people experienced lying in a sickbed for the last one month, number of days lying in a sickbed for the last one month, and activity limitations. CONCLUSION: Health behavior and general health status have a positive correlation.